The Effectiveness of Telegram as an Online Learning Media - Amran, Muhammad; Cale, Woolnough; Jonathan, Bouyea (Journal International of Lingua and Technology, 2024)
Learning media is the main supporting factor that is needed to support the learning process, especially at this time which requires educators to design learning media as an innovation using online media. This study aims to determine the effectiveness of telegram as an online learning media and how important the telegram application is as an online learning media tool. Therefore, the teaching and learning process at this time really needs learning media in order to achieve good learning objectives and for the birth of a new generation that is more innovative and creative. Learning media at this time is very much including the telegram application, this telegram application is a technology application in the form of a chat feature that can be used as a learning media in online learning that can be used either via smartphone or desktop. This type of research is descriptive qualitative research with a literature approach related to the topic discussed. The results of this study explain how the effectiveness of the telegram application as an online learning media.